Left behind in the bounce-back? Informal sector vulnerability in Indonesia’s post-pandemic rebound - Anandari, I Gusti Agung Ayu Apsari; Budiningsih, Ni Ketut; Yudistira, Dewa Bagus Putu Diva Ananda; Putri, Kadek Sri Mirah Yusita (Jurnal Ekonomi & Studi Pembangunan, 2026)
The COVID-19 pandemic has had a profound impact on labor markets, particularly on those working in the informal sector. In Indonesia, informal workers account for more than half of the total workforce and face considerable risks due to the absence of adequate safety nets and limited access to social protection. Considering the large share of informal workers and their vulnerability during crises such as the pandemic, this study seeks to analyze how the pandemic influenced Indonesian workers’ sectoral mobility and to examine its effects on informal workers’ engagement in the social security program (BPJS Ketenagakerjaan). The analysis relies on data from the Survei Angkatan Kerja Nasional (Sakernas), a large-scale household survey conducted regularly by Badan Pusat Statistik (Statistics Indonesia) to monitor the labor market. Specifically, the study uses Sakernas August 2020 and Sakernas August 2022 to compare labor conditions during the pandemic and the post-pandemic period. A binary logit model is employed to assess Indonesian workers’ sectoral mobility and to examine the likelihood of informal workers’ participation in the social security program relative to formal sector workers. The findings indicate that, in the post-pandemic period, the inclination toward formal sector employment has increased, reflecting a rebound after the pandemic. However, the results also show that informal workers remain significantly less likely to participate in the social security program compared to their formal sector counterparts. These findings highlight the need for policy interventions that expand access and incentives for informal workers to join social security schemes and promote pathways from informal to formal employment. Such measures are critical for sustaining labor market recovery, broadening social protection coverage, and reducing vulnerabilities among Indonesia’s workforce.